Lived Experiences of Tabriz University Faculty Members About Information Anxiety and Its Consequences: A Phenomenological Study - Ali Imanzadeh; Maryam Marandi Heidarloo (کتابداری و اطلاع‌رسانی)
Objective: One of the emerging problems and challenges that appeared with the growth and expansion of new technologies and the emergence and growth of new philosophical schools, including post-structuralism, is information anxiety. Post-structuralism is one of the emerging schools that has outstanding views on knowledge and the growth of the rhizomatic knowledge. This type of anxiety, which is mainly a type of epistemological crisis, has arisen in the shadow of the expansion of rhizomatic thinking. The purpose of this research is to analyze the perceptions and experiences of Tabriz University faculty members from information anxiety and its dimensions and consequences.Methodology: The method used in this research is qualitative paradigm and interpretive phenomenology. The participants in this research were 20 faculty members of Tabriz University who were selected through purposive sampling. Data were collected according to in-depth, individual and semi-structured interviews, and the interviews continued until data saturation. After the written implementation of the interviews, the data of the interviews were analyzed based on the hermeneutic approach and based on the method of Dickelman, Tanner and, Allen (1989).Findings: From the analysis of the experiences of faculty members of Tabriz University, 513 codes, 4 main themes: the nature of the profession (job culture, job promotion, professional interaction, knowledge production), Intervening factors of information anxiety (large volume of information and lack of time, emergence of new technologies, fear of losing important information, inability to manage the cognitive system, culture of sharing knowledge and achieving findings) Consequences of information anxiety (anxiety and mental anxiety, feelings of loneliness, decision-making crisis, professional performance and accumulation of professional duties) and information anxiety management strategies (improving cognitive and metacognitive skills, improving information evaluation skills, improving media literacy, self-care and self-restraint and skill management) were achieved.Conclusion: Considering the job nature of university faculty members and the fact that this group is more exposed to information anxiety and this anxiety can affect their job performance, it is possible to adopt strategies such as the development of cognitive and metacognitive skills, information management. So, the promotion of the epistemological system can reduce information anxiety in them.